English Lecturers’ Experiences on Professional Development in Indonesian Polytechnics - Rosmaladewi, Rosmaladewi; Abduh, Amirullah; Basri, Muhammad (Universitas Negeri Makassar, 2020)
The paper aims to depict lecturers’ experiences on the professional development programs in three polytechnics. The study used a qualitative descriptive study employing nine lecturers of English teaching in three different polytechnics. The study finds that lecturers believe that professional development programs as a means for them to improve their knowledge, skills, and expertise. Also, lecturers encounter that professional development programs are not offered equally for lecturers rather than depends on the policy of the top managerial levels. Professional development programs are mostly offered inside the campus for a shorter period rather than offered by external agents that take a longer time. The study recommends that professional development in polytechnics should be done systematically, periodically, and intensively so that lecturers of English in polytechnics can enhance their skills, improve their knowledge, and share their expertise. Further, professional development programs should involve different relevant stakeholders so that they can bring in different expertise and a variety of skills and knowledge so that lecturers of English can fully update with the modern trend of technology. Consequently, they can apply the updated skills and knowledge in their teaching to improve the quality of polytechnic output.